Book review: Wilson, T. (2011). Redirect: The surprising new science of psychological change - Marijn Somers (Scottish Journal of Residential Child Care)
Do you sometimes wonder how effective your work with children and youngsters is? If so, this book will surely give you clues for how to find answers for your questions. If not, it is about time to listen to the wake-up call this book contains.